Expanding the prospects of applying stereoscopic image technology in geometry teaching as a consequence of education informatization - Elena A. Bogdanova; Pavel S. Bogdanov; Sergey N. Bogdanov (RUDN Journal of Informatization in Education)
Problem statement. Informatization of education pointedly affects the development of students' spatial thinking, that fact significantly expands the prospects for applying stereoscopic image technology in geometry teaching. The problem of choosing software environments that allow obtaining high-quality stereoscopic images, as well as the problem of technical equipment selection for the best perception by students of these images in the process of studying stereometry, are relevant. The purpose of this study is to substantiate the appropriateness of using stereoscopic anaglyph images to study stereometry, as well as to identify the most suitable and accessible electronic environment for constructing such images and choosing a technology for transmitting them to students. Methodology. The authors analyze the features of some software environments for constructing stereoscopic images and their application in the study of geometry, identify the main methods for obtaining and transmitting stereoscopic images, and formulate recommendations for introducing stereoscopic image technology into the educational process. Results. The work substantiates the appropriateness of using stereoscopic images in the study of stereometry. It has been established that the cheapest and simplest option for obtaining stereo images is provided by color separation technology, therefore it should be recommended for use in the development of students’ spatial thinking. Analysis of software environments for constructing images with a stereoscopic effect, as well as scientific works devoted to the use of stereoscopic images in the study of various disciplines and in organizing the project-oriented and research activities of students shows that informatization of education significantly expands the prospects for using stereoscopic image technology. In particular, mathematics teachers, using various programs, can quickly and easily create high-quality anaglyph images for geometry teaching. The conducted research made it possible to find out that the optimal tool for this is the GeoGebra system of dynamic mathematics. Conclusion. The work identified electronic environments that are most suitable for constructing high-quality stereoscopic images for the purpose of using them in the geometry teaching process, and selected available technologies for transmitting such images. The issues of developing a methodology for using anaglyph images in stereometry teaching and organizing the training of mathematics teachers to implement this methodology remain relevant.